Felicity : an American girl adventure [videorecording (DVD)] - Sandor, Anna (Screenwriter); Woodley, Shailene; Schneider, John, 1960-; Scheel, Eulala, 1998-; Harden, Marcia Gay; Tripp, Valerie, 1951- (American girls collection., 2005)
Nine-year-old Felicity is a spirited girl growing up in Virginia just before the American Revolution. She knows she's supposed to stay quietly indoors doing girly things, but she yearns for the freedom of the outdoors and for the adventure of riding horses.